Embryo Glue: The Use of Hyaluronan in Embryo Transfer Media - Atkinson, Beth; Woodland, Emma (Seminars in Reproductive Medicine, 2021)
EmbryoGlue is available to patients at many in vitro fertilization clinics, usually at an additional cost. The efficacy of hyaluronan-enriched transfer medium (HETM) is supported by moderate quality evidence that indicates a significant improvement in clinical outcomes such as live birth rates for patients, including poorer prognosis women (i.e., maternal age factor [>35 years] and recurrent implantation failure). An increased multiple pregnancy rate has been reported with the use of HETM; therefore, a single embryo transfer policy should be considered in conjunction with the use of EmbryoGlue. There is no evidence to suggest that HETM has any detrimental impact, and therefore the use of HETM in clinics may be justified for a specific demographic of patients. Further robust evidence, in the form of meta-analyses or large-scale randomized controlled trials, is needed to build a sufficient consensus regarding the benefit of hyaluronan supplementation in embryo transfer media.
Keywords: EmbryoGlue; embryo transfer; hyaluronic acid; hyaluronan